Fisheries Communities and Resource-Use Pattern: Chimdi Lake and its Surrounding Wetlands - Gachhadar, Pramila; Adhikari, A. R.; Chaudhary, R.P. (Our Nature, 2006)
The study was carried out among the fisheries dependent communities of Chimdi lake area, Sunsari district. Major stakeholders of fisheries communities in this lake and its surrounding areas, their expectations and role were identified. Keywords: Chimdi lake, Fisheries Community, Wetlands, Sunsari district doi:10.3126/on.v2i1.323 Our Nature (2004) 2: 35-39